Hypomagnesaemia is absent in children with autosomal dominant polycystic kidney disease. (January 2019) - Seeman, Tomáš; Fořtová, Magdaléna; Sopko, Bruno; Průša, Richard; Pohl, Michael; John, Ulrike
Background: Hypomagnesaemia is present in 40–50% of children with autosomal dominant renal cysts and diabetes syndrome (RCAD). On the contrary, the prevalence of hypomagnesaemia in children with autosomal dominant polycystic kidney disease (ADPKD) has never been examined. We aimed to investigate whether hypomagnesaemia is present in children with polycystic kidney diseases. Methods: Children with cystic kidney diseases were investigated in a cross-sectional study. Serum concentrations of magnesium (S-Mg) and fractional excretion of magnesium (FE-Mg) were tested. Fifty-four children with ADPKD ( n  = 26), autosomal recessive polycystic kidney disease (ARPKD) ( n  = 16) and RCAD ( n  = 12) with median age of 11.2 (0.6–18.6) years were investigated. Results: Hypomagnesaemia (S-Mg < 0.7 mmol/L) was detected in none of the children with ADPKD/ARPKD and in eight children (67%) with RCAD. Median S-Mg in children with ADPKD/ARPKD was significantly higher than in children with RCAD (0.89 vs. 0.65 mmol/L, P  < 0.01). The FE-Mg was increased in 23% of patients with ADPKD/ARPKD (all had chronic kidney disease stages 2–4) and in 63% of patients with RCAD, where it significantly correlated with estimated glomerular filtration rate (r = −0.87, P  < 0.01). Conclusions: Hypomagnesaemia is absent in children with ADPKD or ARPKD and could serve as a marker for differential diagnostics between ADPKD, ARPKD and RCAD in children with cystic kidney diseases of unknown origin where molecular genetic testing is lacking. However, while hypomagnesaemia, in the absence of diuretics, appears to rule out ADPKD and ARPKD, normomagnesaemia does not rule out RCAD at least in those aged <3 years.